2004
DOI: 10.1007/s00125-004-1613-2
|View full text |Cite
|
Sign up to set email alerts
|

Homing of human autoreactive T cells into pancreatic tissue of NOD-scid mice

Abstract: Aims/hypothesis: An important prerequisite for the initiation of pancreatic islet inflammation is the recruitment of pathogenic T cells. We investigated the in vivo migration patterns of human islet-reactive T cell clones after transfer into compromised hosts. Methods: NOD-scid mice were injected with a mixture of human autoreactive T cells and antigen-presenting cells. Survival and migration of T cells was analysed by fluorescenceactivated cell sorter and immunohistochemical analysis of various tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 51 publications
2
24
0
Order By: Relevance
“…This observation coupled with the findings made in the current study, suggest that T cell clones mediating islet graft destruction are directly recruited from PBL. Further evidence indicating that clonotypes found in PBL exhibit a diabetogenic capacity is provided by Roep and colleagues (24) who showed that ␤ cell-specific CD4 ϩ T cell clones prepared from PBL of diabetic patients readily traffick to the islets after transfer into NOD.scid mice.…”
Section: Discussionmentioning
confidence: 98%
“…This observation coupled with the findings made in the current study, suggest that T cell clones mediating islet graft destruction are directly recruited from PBL. Further evidence indicating that clonotypes found in PBL exhibit a diabetogenic capacity is provided by Roep and colleagues (24) who showed that ␤ cell-specific CD4 ϩ T cell clones prepared from PBL of diabetic patients readily traffick to the islets after transfer into NOD.scid mice.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, T-cell clones have been produced from peripheral blood mononuclear cells of newly diagnosed patients that are home to the pancreas of NOD-SCID mice after intravenous transfer, suggesting that autoreactive T-cells circulate at the periphery. 35 Evidence shows that transcriptome analysis will offer new opportunities to identify genes that can be used for early diagnosis of diabetes. Recently, through the combined approach of microarray profiling and genetic linkage analysis, it has been shown that gene expression patterns can be inherited under a variety of conditions across a range of species.…”
Section: Discussionmentioning
confidence: 99%
“…When islets with two or more infiltrating T cells cells of islet infiltrating T cells in a rodent model [10].…”
Section: Expression Of Cxcr3mentioning
confidence: 99%